Patrick R. Duncan: capstone - Duncan, Patrick R., artist (Colorado State University. Libraries, 2014)
The artist's statement: My metalsmithing pieces are inspired by the everyday ordinary. Whether it be at home or in the mountains, I find happiness in simplicity, function and natural beauty. When creating new pieces, I strive to re-create what is seen in everyday life into a piece of simple sophistication that serves its rightful function. My pieces are clean and deliberate, leaving little room for chance. Being an artist in Colorado, I find motivation in nature to create organic and elegant pieces that can be found on a stroll in the park. I rely on nature to tell the story of my piece as I fashion representative pieces into one. My mission is simple: to turn the ordinary into something extraordinary and further serve its destiny in function.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.